PENGARUH HARGA DAN KUALITAS PRODUK TERHADAP KEPUASAN KONSUMEN CHRYSANTHEMUM RESTAURANT PADA HOTEL NALENDRA BANDUNG - Radit Dewandaru, - (2009)
This research has a purpose to identify how the impact of price and product quality toward consumer satisfaction in Chrysanthemum Restaurant at Nalendra Hotel Bandung. The research methods applied in this research are descriptive method and verification. Samples are chosen using accidental random sampling method by involving as much as 100 consumers of Chrysanthemum Restaurant at Nalendra Hotel Bandung as respondents. Data analysis technique in this research is multiple linear regressions. The result of this research proves that price and product quality are positive towards consumer satisfaction as much as 62,3%, on the other hand the rest is influenced by other factors which aren't investigated by the author. Therefore, the improvement on price policy and product quality are needed so that customer experience consumer satisfaction while purchasing product in Chrysanthemum Restaurant at Nalendra Hotel Bandung.